A Legal Analysis of the Gauweiler Case: Between Monetary Policy and Constitutional Conflict. Issue 1 (February 2016) - Tridimas, Takis; Xanthoulis, Napoleon
In Gauweiler, in response to the first ever preliminary reference made by the German Federal Constitutional Court (Bundesverfassungsgericht; FCC), the Court of Justice gave the green light to the ECB's power to selectively purchase Eurozone government bonds in secondary markets (OMT programme). Whilst the Court of Justice sets some limits to European Central Bank's (ECB) authority relying on the golden standard of proportionality, it is a judgment of institutional empowerment. The tensions and instability arising from the separation of competences in monetary and economic policy gravitate to the advantage of the Union. By placing emphasis on the objectives rather than the effects of the programme and linking OMT power to conditionality, Gauweiler builds on Pringle providing normative legitimization to the austerity model whilst granting the ECB a distinct role not only in monetary policy but also in shaping the general economic policy of the Union. The Court of Justice's ruling also indicates a measured but firm response to the dialogue of conflict initiated by the FCC.